Conspicuous and cryptic poison frogs are picky and prefer different meals in syntopy - Sánchez-Loja, Santiago (2023)
The poison frog family (Anura: Dendrobatidae) consists of species with conspicuous (e.g., warning coloration and toxicity or low palatability) and cryptic (e.g., palatable, and inconspicuous coloration) traits. Previous literature suggests that conspicuous, but not cryptic, species require diet specialization in prey high in alkaloids. To test for dietary preferences of poison frog species, we identified, to the lowest possible taxonomic rank, the diets of 21 Epipedobates darwinwallacei (conspicuous) and 22 Hyloxalus awa (cryptic) frogs living in syntopy in the Otongachi Forest in northwestern Ecuador. We then tested for differences in diet assemblage composition, and diet specialization, in these putatively conspicuous and cryptic frogs. Our analyses showed significant differences in the composition of arthropod assemblages consumed by both frog species, which translated into a narrow niche breadth and nine arthropod taxa (out of a total of 18) consumed by both species. Moreover, the index of relative importance, which measures frog’s diet specialization, suggested that E. darwinwallacei, and H. awa prefer specific arthropod taxa, where the former consumes preferentially springtails and mites, while the latter consumes mostly ants and Coleoptera larvae. Thus, contrary to expectations, diet specialization is not a unique characteristic of the species with conspicuous traits when living in syntopy.